2013
DOI: 10.1074/jbc.m113.496968
|View full text |Cite
|
Sign up to set email alerts
|

Role for Human Mediator Subunit MED25 in Recruitment of Mediator to Promoters by Endoplasmic Reticulum Stress-responsive Transcription Factor ATF6α

Abstract: Background: ATF6␣ recruits Mediator to activate endoplasmic reticulum stress response genes. Results: Mediator subunit MED25 contains an ATF6␣ binding site. Conclusion:The ATF6␣-MED25 interaction contributes to Mediator recruitment to genes. Significance: Learning how DNA binding transcription activators recruit coactivators to genes is important for understanding gene regulatory mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 45 publications
3
46
0
Order By: Relevance
“…Interestingly, the novel p.Ile173Thr variant identified in this study, in MED25 , is located in the same functional domain, the von Willebrand-associated domain, as the p.Arg140Trp and p.Tyr39Cys mutations reported in the patients with Basel-Vanagaite-Smirin-Yosef syndrome and syndromic intellectual disability. The von Willebrand-associated domain is known to direct the incorporation of the protein into the Mediator complex [Sela et al, 2013]. In addition, homology studies clearly show the conserved nature of the residue across species.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the novel p.Ile173Thr variant identified in this study, in MED25 , is located in the same functional domain, the von Willebrand-associated domain, as the p.Arg140Trp and p.Tyr39Cys mutations reported in the patients with Basel-Vanagaite-Smirin-Yosef syndrome and syndromic intellectual disability. The von Willebrand-associated domain is known to direct the incorporation of the protein into the Mediator complex [Sela et al, 2013]. In addition, homology studies clearly show the conserved nature of the residue across species.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, functional studies showed the importance of MED25 in the activation of transcription by several transcription factors, including the retinoic acid receptor (RARα),27 orphan receptor (HNF4α),28 chondrogenic factor (Sox9),29 PEA3 group members,30 activating transcription factor 6 (ATF6α)31 and estrogen receptor α 32. These factors are involved in different developmental processes and they control multiple metabolic pathways,28 32 development of motor and sensory neurons,33 response of human cells to endoplasmic reticulum stress, which are critical for cell survival and defects can cause neurodegeneration34 and chondrogenesis 29…”
Section: Discussionmentioning
confidence: 99%
“…In the case of many, but not all, HNF4␣ inducible genes, MED25 recruits the Mediator complex, pol II (11), and as the present study shows, enzymes involved in modifying the chromatin structure. An enrichment of the CYP2C9 HNF4␣ binding region by MED1 and MED14 suggests that a multimeric Mediator complex is recruited in coordination with MED25, with MED25 serving as one of the Mediator docking sites for specific transcriptional activation domains of transcription factors (49,50). This recruitment constitutes the initial step of MED25-mediated activation of HNF4␣ target genes prior to full PIC formation.…”
Section: Discussionmentioning
confidence: 99%